2012
DOI: 10.1007/s10528-011-9492-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Genetic Diversity of Vitis vinifera cv. Kabarcik Populations from the Coruh Valley Using SSR Markers

Abstract: Northeastern Turkey is recognized as one of the most important germplasm centers for the grape in the world. In the present study, simple sequence repeat markers were used to investigate the genetic diversity between four Vitis vinifera cv. Kabarcik populations sampled from the Coruh Valley in Turkey, at altitudes of 800-1,150 m. The mean observed number of alleles per locus varied from 2 (loci VVMD7 and VVMD24) to 6 (VVS2) among populations. The population from the highest altitude showed the greatest average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…As shown in table 2, VMC5G1 locus showed the lowest number of different alleles (Na) (three alleles) and VMC1C10 locus observed the highest (nine alleles) with a total of 63 alleles considering all loci (in an average of 5.25 alleles). Previous studies on grapes confirmed that the VVS2 locus was given the highest number of alleles (Nunez et al, 2004;Şelli et al, 2007;Tangolar et al, 2009;Agar et al, 2012). The average number of different alleles in the present study was 5.25, which is relatively similar to the average number of alleles observed by previous studies (Emanuelli et al, 2013).…”
Section: Resultssupporting
confidence: 90%
“…As shown in table 2, VMC5G1 locus showed the lowest number of different alleles (Na) (three alleles) and VMC1C10 locus observed the highest (nine alleles) with a total of 63 alleles considering all loci (in an average of 5.25 alleles). Previous studies on grapes confirmed that the VVS2 locus was given the highest number of alleles (Nunez et al, 2004;Şelli et al, 2007;Tangolar et al, 2009;Agar et al, 2012). The average number of different alleles in the present study was 5.25, which is relatively similar to the average number of alleles observed by previous studies (Emanuelli et al, 2013).…”
Section: Resultssupporting
confidence: 90%
“…Moreover, in a set of six SSR markers from four cultivated populations of V. vinifera cv. containing 60 individuals, expected heterozygosity varied from 0.126 (VVMD7) to 0.790 (VVS2), with the overall average of 0.574 (Agar et al, 2012). da Silva et al (2015) reported that the numbers and frequencies of alleles in genetic diversity studies affect the marker heterozygosity.…”
Section: Nuclear Microsatellites Polymorphism Among the Grapevine Accessionsmentioning
confidence: 99%
“…Based on their PIC, the most polymorphic loci were VVSMD25 (0.87) followed by VVS1 (0.85) and ISV3 (0.81), whereas VVS3 (0.50), ISV3 (0.50) and VVSMD6 (0.55) showed the lowest PIC (Table 3). Several studies on Vitis genus indicated that the most informative SSR markers included VVS2, VVMD5, VVS5, VVMD14, VVMD28, and VVMD36 (Agar et al, 2012;Borrego et al, 2001;Crespan and Milani, 2001;Ibañez et al, 2003;Lefort and Roubelakis-Angelakis, 2001).…”
Section: Nuclear Microsatellites Polymorphism Among the Grapevine Accessionsmentioning
confidence: 99%
“…Most previous studies have focused on V. vinifera L. cultivars from a single location (Agar et al, 2012), which limits the utilization of the species to some extent. In this work, we selected 49 grape germplasm accessions originating from several different countries and investigated their genetic diversity and evolutionary relationships using 19 SSR markers.…”
Section: Introductionmentioning
confidence: 99%